La autocrítica mediática en la prensa francesa tras el 11 de septiembre - Santos Sáinz, María (Estudios sobre el Mensaje Periodístico, 2002)
The treatment from the medias on September 11th has gave rise in France a selfcriticism thought, about the mass media role playing. Some authors agree in the fact that certain error already make in the mass media during the Gulf war and the Kosovo war has been repeated. All this points emphasize the difficulty of the autonomy in the media speech, and the needs of some kind of distancing from the journalist in relation with the State, with the events, and with the political and military power, to do not fall into a Manichaean and emotional speech.
Keywords: Mass media; French journalism; informative sources; Journalistic opinion; 11 of September